Factors affecting tax compliance behavior of business households and individuals with e-commerce activities: A study in Vietnam - Vu, Thi Thanh An; Pham, Tien Dat; Phan, Thi Hang Nga (Journal of Finance - Marketing Research, 2025)
The goal of this article is to study the factors affecting tax compliance of individuals and households with businesses on e-commerce platforms. The study conducted a survey of 700 votes corresponding to 700 taxpayers, representing 700 business households/individuals in 07 provinces and cities of the country. The results collected 665 suitable answer votes, the rate reached 95.00%. Through the results of scale reliability analysis, exploratory factor analysis, affirmative factor and linear structure model. The results have identified seven influencing factors and are arranged according to standardized regression coefficients, respectively: Psychological factors, social factors, economic factors, characteristics of tax authorities, legal factors and tax policies, etc the characteristics of the operation of the taxpayer, and the operation of the investment service. From the results of the study, the authors proposed a number of policy implications to contribute to improving the tax compliance behavior of business households/individuals with e-commerce activities in Vietnam in the coming time.